Synthesis and characterization of silver and silver selenide nanoparticles and their incorporation into polymer fibres using electrospinning technique - More, Dikeledi Selinah (Vaal University of Technology, 2015)
Here, we report the synthesis and characterization of silver (Ag) and silver selenide (Ag2Se) nanoparticles using the metal-organic route method. This method involves the reduction of selenium powder and silver nitrate in the presence of trioctylphosphine as a solvent. Tri-n-octylphosphine oxide (TOPO) and hexadecylamine (HDA) were used in the study as capping molecules. The optical properties of the as-prepared nanoparticles were studied using UV-Visible and photoluminescence spectroscopy (PL). Transmission electron microscopy (TEM) and X-ray powder diffraction (XRD) were used to study the structural properties. The effect of capping molecules and temperature were investigated on the growth of the nanoparticles. The prepared nanoparticles seem to depend on the reaction temperature were the increase in temperature led to an increase in particle sizes. The growth of the as-prepared TOPO-capped Ag2Se nanoparticles was influenced by temperature, this was evident when the temperature was increased, the nanoparticles evolved from sphere to hexagonal shape. TOPO-capped nanoparticles showed the tendency of agglomeration with increase in temperature compared to HDA-capped nanoparticles. The X-ray diffraction results showed peaks which were identified as due to α-Ag2Se body centered cubic compound for both TOPO/HDA-capped Ag2Se nanoparticles. Some evidence of impurities were observed in the XRD analysis and indexed to metallic silver. HDA-capped Ag nanoparticles were found to be affected by temperature variation. The prepared nanoparticles were characterized with UV-Vis spectroscopy and transmission electron microscopy. XRD analysis was not performed due to small yield obtained. The absorption spectra of HDA-capped Ag nanoparticles at different temperatures show a surface Plasmon resonance (SPR) band in the regions 418 - 428 nm. Uniform spherical shapes were obtained for both 130 and 190 °C and fewer particles were obtained at 160 °C. The synthesis of TOPO–capped Ag nanoparticles was unsuccessful since none of the particles were isolated from the solution due to its lower capping ability or it may be that TOPO is binding too strongly to Ag. The polymer nanofibres were electrospun using electrospinning technique. Parameters such as concentration and voltage were investigated. These parameters significantly affect the formation of fibre morphology. PVP and PMMA polymers were used for this study. The electrospun composite fibres were characterized using UV-Visible spectroscopy, scanning electron microscopy (SEM), Thermal gravimetric analysis (TGA), X-ray diffraction (XRD) and Fourier transformer infrared (FTIR) spectroscopy. The SEM results show that increasing the polymer concentration resulted in increased fibre diameters. Hence increasing the voltage decreases the fibre diameters. Ag2Se nanoparticles were incorporated into PVP and PMMA and electrospun using electrospinning to produce composite fibres. Their addition into PVP polymer fibres improved the fibre’s uniformity and further decreased their diameters. The SEM of composite fibres for PMMA is not shown. The absorption bands for PVP composites fibres show a blue shift from the pure Ag2Se nanoparticles, whereas the one for PMMA show a red shift from the pure Ag2Se nanoparticles. Both the composite fibres for PVP and PMMA show a blue shift from the bulk of Ag2Se. The XRD analysis of the composite fibres shows no significant effect upon addition of Ag2Se nanoparticles on the amorphous peak of the PVP polymer, whereas on the PMMA, it shows peaks which were due to the face centered cubic phase of Ag. The FTIR spectra of the composite fibres and pure polymers (PVP and PMMA) gave almost identical features. TGA curves show no significant effect on the thermal properties of the PVP polymer and its composites, however, on the PMMA composite fibres it show an increase in the thermal stability of the polymers upon addition of Ag2Se nanoparticles. The study was based on silver nanoparicles and its antibacterial activities. One of the synthetic challenges for silver nanoparticles is their solubility and yield. Selenide was introduced in the study to improve such shortcomings of silver nanoparticles and also for possible improved properties, chemical stability and increased activity against bacteria. The selenide group on the metal also provides stronger chemical interaction between the nanoparticles and the polymer. Therefore, the intension was to use these nanoparticles into polymer fibres for potential use in wound dressing.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: Silver nanoparticles; Silver selenide nanoparticles; Trioctylphosphine; HDA-capped nanoparticles; Capping molecules; PVP polymer fibres; Polymer nanoparticles; Electrospinning; Fibre morphology; 620.192; Nanoparticles.; Dissertations, Academic -- South Africa.